Strategi pelayanan pastoral untuk mencegah perilaku seks bebas di kalangan remaja - Pasaribu, Nehemia (PNEUMATIKOS: Jurnal Teologi Kependetaan, 2024)
Free sex has become one of the major issues faced by teenagers today. Free sex is caused by internal factors such as hormonal change, curiositty and the urge to try new things as well as external factors such as parental influence, peer pressure, and media impact. This study employs a descriptive qualitative method to formulate effective pastoral care strategies to prevent free sex behavior among teenagers. The proposed strategies include building personal connections based on love, enhancing teenagers’ resilience through faith development, creating a positive and supportive community, and fostering close collaboration with parents. This research aims to provide practical guidelines for spiritual leaders in mentoring and guiding teenagers toward lives aligned with Christian values.